Analysis Of Ict Media Development In The Learning Process At Mi Nurul Islam Plangkapan Towards The Transformation Of Indonesia's Golden Education 2045 - Musonif, Irfan; Pranoto, Ahmad Hadi; Nurhuda, Abid; Lathif, Nur Muhammad; Ismail, Muhammad Faqihudin (Edelweiss : Journal Of Innovation In Educational Research, 2026)
This study aims to describe the development and implementation of Information and Communication Technology (ICT) media in learning at MI Nurul Islam Plangkapan as part of the transformation toward Golden Indonesia 2045. This research employed a qualitative field approach with data collected through interviews, observations, and documentation. The results indicate that teachers, the headmaster, and students showed positive responses toward the use of ICT in the learning process. Teachers utilized digital media such as PowerPoint, Canva, and Quizizz to create more engaging and interactive learning experiences. Although challenges such as limited facilities and unstable internet connections remain, ICT integration has enhanced students’ motivation, participation, and 21st-century learning competencies. It is concluded that ICT implementation in elementary madrasahs contributes to improving learning quality and supports the national vision of Digital Madrasah toward Golden Indonesia 2045.